RNA-seq reveals that anti-obesity irisin and triiodothyronine (T3) hormones differentially affect the purinergic signaling transcriptomics in differentiated human adipocytes - Mathias, Lucas Solla [UNESP]; Herman-de-Sousa, Carina; Cury, Sarah Santiloni [UNESP]; Nogueira, Célia Regina [UNESP]; Correia-de-Sá, Paulo; de Oliveira, Miriane [UNESP] (Elsevier, 2023)
The anti-obesity thyroid hormone, triiodothyronine (T3), and irisin, an exercise- and/or cold-induced myokine, stimulate thermogenesis and energy consumption while decreasing lipid accumulation. The involvement of ATP signaling in adipocyte cell function and obesity has attracted increasing attention, but the crosstalk between the purinergic signaling cascade and anti-obesity hormones lacks experimental evidence. In this study, we investigated the effects of T3 and irisin in the transcriptomics of membrane-bound purinoceptors, ectonucleotidase enzymes and nucleoside transporters participating in the purinergic signaling in cultured human adipocytes. The RNA-seq analysis revealed that differentiated adipocytes express high amounts of ADORA1, P2RY11, P2RY12, and P2RX6 gene transcripts, along with abundant levels of transcriptional products encoding to purine metabolizing enzymes (ENPP2, ENPP1, NT5E, ADA and ADK) and transporters (SLC29A1, SCL29A2). The transcriptomics of purinergic signaling markers changed in parallel to the upsurge of “browning” adipocyte markers, like UCP1 and P2RX5, after treatment with T3 and irisin. Upregulation of ADORA1, ADORA2A and P2RX4 gene transcription was obtained with irisin, whereas T3 preferentially upregulated NT5E, SLC29A2 and P2RY11 genes. Irisin was more powerful than T3 towards inhibition of the leptin gene transcription, the SCL29A1 gene encoding for the ENT1 transporter, the E-NPP2 (autotaxin) gene, and genes that encode for two ADP-sensitive P2Y receptors, P2RY1 and P2RY12. These findings indicate that anti-obesity irisin and T3 hormones differentially affect the purinergic signaling transcriptomics, which might point towards new directions for the treatment of obesity and related metabolic disorders that are worth to be pursued in future functional studies.
Keywords: Adenosine; ATP; Human adipocytes; Irisin; Obesity; Purinergic signaling; Thyroid hormones